PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL ACTIVITY OF NEOCARYAMACROPHYLLA LEAVES EXTRACT - Isaka, Ibrahim; Gumel, Ahmad Mohammed; Muhammad, Humaira Ya’u; Kemi, Amoo Florence (LIFE: International Journal of Health and Life-Sciences, 2017)
The frequency of life-threatening infections caused by pathogenic microorganisms has increased worldwide and is becoming an important cause of morbidity and mortality especially in developing countries with lower health status indices. The increasing prevalence of multi-drug resistant strains of bacteria raised the specter of untreatable bacterial infections and adds urgency to the search for new therapeutic strategies. Along this line, this study investigated phytochemical screening of Neocaryamacrophylla extract using GC-MS and Antibacterial screening of the extract using agar well diffusion method. Three microorganisms were used namely; Escherichia coli, Klebsiellapneumoniae and Staphylococcus aureus. The susceptibility tests result showed inhibition range of 24 and 13mm against K. pneumoniae at 20 and 10 mg/ml illustrating it to be the most sensitive organism. The least was E. coli, (16 and 7mm at 20 and 10 mg/ml). Similarly, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extract indicated K. pneumoniae to be more susceptible followed by S. aureus and E. coli as the least susceptible species. Generally, in all the model organisms tested, the susceptibility was observed to be concentration dependent. The test results indicated that leaves extract of N. macrophylla has antimicrobial potency and could be used as an alternative antimicrobial therapy.